✨✨5∅ Pôints ✨✨
❤ plzz help me guys ❤
✌ ♥ Føllow me ♥ ✌
✔ Quality answers ✔
Attachments:
![](https://hi-static.z-dn.net/files/da8/3bdac78cd12f4892f009ae1b59fdea6c.jpg)
Answers
Answered by
3
x^3 - x - 2x +2
x( x^2 -1) -2( x-1)
x( x-1)(x+1) -2 ( x-1)
x-1)( x(x+1) -2))
( x-1)( x^2 + x -2)
( x-1)( x^2 - x + 2x -2)
( x-1)( x( x-1) + 2 + x-1))
( x-1)( x-1)( x+2)
x( x^2 -1) -2( x-1)
x( x-1)(x+1) -2 ( x-1)
x-1)( x(x+1) -2))
( x-1)( x^2 + x -2)
( x-1)( x^2 - x + 2x -2)
( x-1)( x( x-1) + 2 + x-1))
( x-1)( x-1)( x+2)
Answered by
3
Answer:
(x - 1)²(x + 2)
Step-by-step explanation:
Given Equation is x³ - 3x + 2
= x³ + x² - x² - 2x - x + 2
= x³ + x² - 2x - x² - x + 2
= x(x² + x - 2) - 1(x² + x - 2)
= (x - 1)(x² + x - 2)
= (x - 1)(x² - x + 2x - 2)
= (x - 1)(x(x - 1) + 2(x - 1))
= (x - 1)(x - 1)(x + 2)
= (x - 1)²(x + 2).
Hope it helps!
Similar questions
Science,
8 months ago
Geography,
8 months ago
Math,
1 year ago
Chemistry,
1 year ago
Psychology,
1 year ago